Kampaṉ kaṇṭa ulakiyal - Arasumani, Kanakasabai, 1930- (Cāntimati Piracuram veḷiyīṭu, 1978)
On the human relationships of Kampar, author of the Kamparāmāyaṇam, 9th century Tamil epic of Rama, Hindu deity.